Inherent vs. Induced Loop Gain Abnormalities in Obstructive Sleep Apnea - Deacon-Diaz, Naomi; Malhotra, Atul (Frontiers in Neurology, 2018)
Unstable ventilatory chemoreflex control, quantified as loop gain, is recognized as one of four key pathophysiological traits that contribute to cause obstructive sleep apnea (OSA). Novel treatments aimed at reducing loop gain are being investigated, with the intention that future OSA treatment may be tailored to the individual's specific cause of apnea. However, few studies have evaluated loop gain in OSA and non-OSA controls and those that have provide little evidence to support an inherent abnormality in either overall chemical loop gain in OSA patients vs. non-OSA controls, or its components (controller and plant gain). However, intermittent hypoxia may induce high controller gain through neuroplastic changes to chemoreflex control, and may also decrease plant gain via oxidative stress induced inflammation and reduced lung function. The inherent difficulties and limitations with loop gain measurements are discussed and areas where further research are required are highlighted, as only by understanding the mechanisms underlying OSA are new therapeutic approaches likely to emerge in OSA.